POLITIK PENDIDIKAN PADA MASA DAULAH ABBASIYAH (KASUS MADRASAH NIZHAMIYAH DI BAGHDAD) - Ali Murtopo (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
The Political will determine advancement and deterioration for education. No matter what achieved or any form of education, both positive and negative is part of the process of interest and political intrigues. Scientific movements of changes and transformation of society is always driven by political patronise. In this context, politics appears to be the main support of the achievement of triumph the education system.